SWHEI: A New Approach to Measure Policy Effectiveness for Solar Water Heaters - Bruno Luis-Badillo; Daniel Guerrero-Hoyos; Gerardo A. Escamilla; Luis Rojas-Solórzano (International Journal of Renewable Energy Development, 2022)
In the context of the global energy transition, governments design and apply renewable energy policies as tools to replace fossil fuel sources for the heating end-use sector, which represents half of the global total final energy consumption (TFEC). In the last two decades, large deployments of solar thermal technologies, such as solar water heaters (SWH), have helped renewable energy penetrate the heating sector. To be successful, their adoption must be supported by effective policies; however, measuring the effectiveness of a particular policy is a complex task. Some studies design and propose indicators to measure this effectiveness but are difficult to replicate or adapt to specific markets. This work submits a novel policy-outcome effectiveness indicator, the Solar Water Heater Effectiveness Indicator (SWHEI), based on equipment deployment (installed capacity per capita, installed capacity growth) and the solar energy potential of each country, constructed using publicly available data to ensure replicability and universal utilization. The overall SHWEI values for the period 2003–2019 are low, reflecting the current low adoption of solar technologies, but show regional clusters of good performance, such as in Europe. Barbados achieved the maximum value of 6.9, which reflects its outstanding performance, driven by its installed capacity per capita. The analysis shows that the SWHEI is particularly useful to determine policy ineffectiveness while confounding factors could camouflage policy effectiveness. The SWHEI-active SWH policies matrix can help policymakers identify courses of action. Policymakers could 1) use market-entry policy instruments in undeveloped SWH markets (segment C, no policies in place); 2) review and improve failing SWH policies (segment D); 3) propose randomized controlled trials to study causal relationships between SWH policies and large SWHEI (segments A and B with policies in place); and 4) regulate successful markets, allowing for continued organic growth (segment A, no policies).